Tofacitinib, an oral Janus kinase inhibitor, for the treatment of chronic plaque psoriasis: results from two randomized, placebo‐controlled, phase III trials. (1st October 2015) - Papp, K.A.; Menter, M.A.; Abe, M.; Elewski, B.; Feldman, S.R.; Gottlieb, A.B.; Langley, R.; Luger, T.; Thaci, D.; Buonanno, M.; Gupta, P.; Proulx, J.; et al.
Summary: Background: Tofacitinib is an oral Janus kinase inhibitor being investigated for psoriasis. Objectives: To determine the 16‐week efficacy and safety of two oral tofacitinib doses vs. placebo in patients with moderate‐to‐severe chronic plaque psoriasis. Methods: Patients in two similarly designed phase III studies (OPT Pivotal 1, NCT01276639, n = 901; OPT Pivotal 2, NCT01309737, n = 960) were initially randomized 2 : 2 : 1 to tofacitinib 10 or 5 mg or placebo, twice daily. Coprimary efficacy end points (week 16) included the proportion of patients achieving Physician's Global Assessment (PGA) of 'clear' or 'almost clear' (PGA response) and the proportion achieving ≥ 75% reduction in Psoriasis Area and Severity Index (PASI 75). Results: Across OPT Pivotal 1 and OPT Pivotal 2, 745 patients received tofacitinib 5 mg, 741 received tofacitinib 10 mg and 373 received placebo. At week 16, a greater proportion of patients achieved PGA responses with tofacitinib 5 and 10 mg twice daily vs. placebo (OPT Pivotal 1, 41·9% and 59·2% vs. 9·0%; OPT Pivotal 2, 46·0% and 59·1% vs. 10·9%; all P < 0·001). Higher PASI 75 rates were observed with tofacitinib vs. placebo (OPT Pivotal 1, 39·9%, 59·2% and 6·2%, respectively, for tofacitinib 5 and 10 mg twice daily and placebo; OPT Pivotal 2, 46·0%, 59·6% and 11·4%; all P < 0·001 vs. placebo). Adverse event (AE) rates appeared generally similar across groups; rates of serious AEs, infections, malignancies and discontinuations due to AEs were low. Twelve patients reported herpes zoster across the tofacitinib treatment groups in both studies vs. none in the respective placebo groups. The most common AE across groups was nasopharyngitis. Conclusions: Oral tofacitinib demonstrated significant efficacy vs. placebo during the initial 16 weeks of treatment in patients with moderate‐to‐severe psoriasis. Safety findings were consistent with prior studies.